DAMPAK DIGITALISASI TERHADAP HUKUM KONTRAK: ANALISIS TERHADAP PERJANJIAN SMART CONTRACT - Sylvia Purborini, Vivi; Bagus Suryanatha, Ida (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2024)
Digitalization has significantly changed the way contracts are executed, especially with the emergence of smart contracts. The positive impact of digitalization on contract law cannot be denied, however, there are also challenges and controversies that need to be addressed wisely. Qualitative research methods will be the main approach in exploring the impact of digitalization on contract law in smart contract analysis. By utilizing observations and document analysis, this research will explore an in-depth understanding of the implementation of smart contracts in the context of contract law. The practical implication is the need to update contract law regulations that accommodate technological developments, while the theoretical implication is the need for an in-depth understanding of the characteristics of smart contracts and their impact on traditional contract. the need to update contract law regulations to accommodate technological developments, especially in the use of smart contracts. Meanwhile, the theoretical implication is the importance of a deep understanding of the characteristics of smart contracts and their impact on traditional contracts in order to minimize potential legal conflicts. Keywords: Digitalization, Contract Law, Agreements, Smart Contracts